Impact on the incorporation of metals in physicochemical and antimicrobial properties in films based on arrowroot starcha - Antonio Carlos Pereira de Menezes Filho; Matheus Vinicius Abadia Ventura; Carlos Frederico de Souza Castro; Rogério Favareto; Marconi Batista Teixeira; Frederico Antônio Loureiro Soares (La Granja: Revista de Ciencias de la Vida)
New biodegradable packaging has been developed from renewable sources, mainly of vegetable origin. Arrowroot starch has been recently used to produce high-quality biodegradable films capable of behaving well when incorporating oils, extracts, metal, and metal nanocomposites. The study aimed to verify the impact of incorporating metals in the sulfate and chloride forms in a biopolymeric matrix from arrowroot starch in terms of biodegradability, physicochemical and microbiological parameters. Different arrowroot films were produced to incorporate solutions with a concentration of 1 Mol L-1 of sulfate and chloride metals. The action of biodegradability in soil, UV transmittance, and visible light were observed in UV-Vis spectrophotometry and antimicrobial action on Escherichia coli, Staphylococcus aureus, Salmonella serovar Typhimurium, and Salmonella serovar Enteritidis. Good results were obtained, such as biodegradability time between 81.70 to 100 % (30 days), a low transmission rate of UV radiation and visible light between 250 to 890 nm, high capacity for bacterial inhibition between 22.08 to 10.05 mm for E. coli, among 25.59 to 11.10 mm for S. aureus, between 22.14 to 11.66 mm for S. serovar Typhimurium and between 21.11 to 8.26 mm for S. serovar Enteritidis. It is concluded that the biodegradable films of arrowroot starch incorporated with metals showed potential in all the evaluated tests, thus characterizing possible new products for different uses, such as low time available in the environment, preservation of the characteristics of special products, and antimicrobial capacity.